Analysis of Environmental Social Governance (ESG) Impact Study on Local Cultural Wisdom: A Case Study at PT Bukit Asam Tanjungenim, South Sumatera, Indonesia - Yulianti, Yulianti (HM Publisher, 2024)
The implementation of Environmental Social Governance (ESG) in Indonesia is increasingly being implemented, including in the mining sector. PT Bukit Asam (PTBA) as one of the largest coal mining companies in Indonesia has implemented ESG in its operations. This research aims to analyze the impact of PTBA's ESG implementation on local cultural wisdom in the Tanjungenim area, South Sumatera. This research uses a qualitative method with a case study approach. Data collection was carried out through interviews with key informants, participant observation and documentation. Data were analyzed using qualitative data analysis techniques. The research results show that PTBA's ESG implementation has both positive and negative impacts on local cultural wisdom. The positive impacts include: (1) increasing public awareness about the importance of protecting the environment; (2) increasing community participation in decision making related to the environment; (3) improving the quality of life of the community through community empowerment programs. The negative impacts include: (1) changes in local cultural values due to external cultural influences; (2) the occurrence of social conflict between indigenous communities and companies; (3) loss of local traditions and culture due to modernization. In conclusion, PTBA's ESG implementation has positive and negative impacts on local cultural wisdom. Efforts need to be made to maximize the positive impacts and minimize the negative impacts.